(13+5y)-(16y-10)=

Simple and best practice solution for (13+5y)-(16y-10)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (13+5y)-(16y-10)= equation:


Simplifying
(13 + 5y) + -1(16y + -10) = 0

Remove parenthesis around (13 + 5y)
13 + 5y + -1(16y + -10) = 0

Reorder the terms:
13 + 5y + -1(-10 + 16y) = 0
13 + 5y + (-10 * -1 + 16y * -1) = 0
13 + 5y + (10 + -16y) = 0

Reorder the terms:
13 + 10 + 5y + -16y = 0

Combine like terms: 13 + 10 = 23
23 + 5y + -16y = 0

Combine like terms: 5y + -16y = -11y
23 + -11y = 0

Solving
23 + -11y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-23' to each side of the equation.
23 + -23 + -11y = 0 + -23

Combine like terms: 23 + -23 = 0
0 + -11y = 0 + -23
-11y = 0 + -23

Combine like terms: 0 + -23 = -23
-11y = -23

Divide each side by '-11'.
y = 2.090909091

Simplifying
y = 2.090909091

See similar equations:

| M/-3-12=-5 | | M+3=2m-5 | | 5(s+15)=95 | | 31/3=1/2t | | 1/2(16-i)=11/2i | | 1+3x=4x-6 | | 16=4(r-83) | | -(X-2)=-5X+42 | | 31=8n+-1 | | Z+4(2z+3)=14 | | 25=13-3x | | 6x-4x+10x=49+5x | | 14-12V=4(1-5V)+8V | | -(k-10.9)=1.4k-1.1 | | 3x(-x-3)-2=x(3x-4)+13 | | 65=5(y-86) | | 7x-9=19+x | | -7(3+6V)=-189 | | -6/7-1/7= | | (6x)x2/3 | | 4x+2+5x+3=3x+53 | | 5x+6y+9x= | | -330=10(-5x-3) | | 4x+8x+6x-24=x | | 5-(3-x)=6.5 | | M=682287/967540 | | -10(X-6)=6(10+2X) | | -4x+4(3x-13)=-140 | | 4x+8x+6x=24 | | -4(3-3m)=-37+7m | | 2(g-h)=b+y | | 9/7*-9/5 |

Equations solver categories